Tracheal Intubation - Riza Hakan Erbay (IntechOpen, 2018)
Endotracheal intubation is a mandatory practice in the anesthesiologic management of surgical procedures, cardiopulmonary resuscitation, life-saving procedures in the emergency department, and medical procedures, and it involves many medical issues such as anesthesiology, surgery, and pulmonary diseases. This book deals with the basic principles of hypoxia and oxygenation in terms of functional airway anatomy and intubation requirements as well as difficult airway algorithms.
English
Keywords: Medicine; Surgery; Anesthesiology; Health Sciences